Gambaran Tingkat Pengetahuan tentang Sadari dan Satistri pada Mahasiswa Fisioterapi Poltekkes Kemenkes Surakarta - Dwi Nur Astuti; Triyana Triyana (Politeknik Kesehatan Kemenkes Surakarta, 2026)
Background: Breast cancer is one of the leading causes of morbidity and mortality among women worldwide. Early detection through breast self-examination (BSE) and clinical breast examination (CBE) plays a crucial role in reducing delayed diagnosis. Physiotherapy students, as future healthcare professionals, are expected to have adequate knowledge regarding early detection of breast cancer. Objectives: This study aimed to describe the level of knowledge about breast self-examination (BSE) and clinical breast examination (CBE) among physiotherapy students at Poltekkes Kemenkes Surakarta. Methods: This study employed a descriptive design with a cross-sectional approach. The sample consisted of physiotherapy students selected using purposive sampling technique with total subjek 100 students. Data were collected using a validated questionnaire and analyzed descriptively using frequency distribution and percentages. Results: The results showed that most respondents had a moderate to good level of knowledge; however, some students still demonstrated limited understanding, particularly regarding the procedures and timing of BSE and CBE. Conclusion: In conclusion, the level of knowledge among physiotherapy students regarding early detection of breast cancer is generally adequate, but further educational interventions are needed to improve their understanding comprehensively. Keywords : Breast Self-Examination, Elinical Breast Examination, Knowledge, Physiotherapy Students, Cancer.